2019
DOI: 10.1002/cptc.201900069
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Selective Ring Hydrogenation of Phenol to Cyclohexanone over a Palladium‐Loaded Titanium(IV) Oxide under Hydrogen‐Free Conditions

Abstract: Photocatalytic ring hydrogenation of phenol proceeded in an aqueous suspension of palladium-loaded TiO 2 at room temperature in the presence of oxalic acid as a hole scavenger, and cyclohexanone was produced in a high yield (90 %) without the use of hydrogen gas. Cyclohexanone was formed via keto-enol tautomerism of cyclohexenol. The effects of hole scavengers and solvents on the hydrogenation of phenol can be explained by the adsorption behaviour of phenol and hole scavengers in the solvents. Over a Pd-TiO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…It is important to highlight that alcohols have been reported as good HO • scavengers but their presence can also alter the adsorption mechanism of ACE since they may compete with ACE for the initial adsorption sites, which trigger the photocatalytic reactions. Oxalic acid has been reported as a good inhibitor of photo-generated holes (h + ) [ 59 , 60 ]. Under the presence of oxalic acid, the photocatalytic performance was negligible and the k Obs obtained was very close to that reached under photolysis, therefore, highlighting the importance of the holes in the photocatalytic process.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to highlight that alcohols have been reported as good HO • scavengers but their presence can also alter the adsorption mechanism of ACE since they may compete with ACE for the initial adsorption sites, which trigger the photocatalytic reactions. Oxalic acid has been reported as a good inhibitor of photo-generated holes (h + ) [ 59 , 60 ]. Under the presence of oxalic acid, the photocatalytic performance was negligible and the k Obs obtained was very close to that reached under photolysis, therefore, highlighting the importance of the holes in the photocatalytic process.…”
Section: Resultsmentioning
confidence: 99%
“…As the reaction temperature was increased, the rate of Py formation increased. Thermal acceleration effects in photocatalytic reactions have been observed in some cases: 1) surface reactions over a metal cocatalyst after the charge separation by band-gap excitation is the rate-determining step [38,39] and 2) desorption of a product from the photocatalyst is more predominant than desorption of a starting substance at elevated temperatures. [28] Since Py desorption was accelerated more than PyNO desorption at a high temperature, [28] the present results can be explained by the effect of the temperature on desorption of Py.…”
Section: Effects Of Different Reaction Temperaturesmentioning
confidence: 99%
“…[17] Metal oxides were also used as supports because of their potential to participate in the electron transfer process in the catalytic process. [18][19][20][21] Chen et al [21] reported that the TiO 2 nano-islands with oxygen vacancies could improve the Pd dispersion, make more Pd elements on the support surface, strengthen the antioxidizability of Pd and induce electron-rich Pd NPs. The rare earth oxide has aroused great interest in the use of catalytic reaction due to its unique characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…As support, although the activated carbon with a large specific surface area, it was ineffective to the adsorption model of the substrate due to surface neutrality, and generally unsatisfactory in conversion and selectivity [17] . Metal oxides were also used as supports because of their potential to participate in the electron transfer process in the catalytic process [18–21] . Chen et al [21] .…”
Section: Introductionmentioning
confidence: 99%